The Generative Logic, Theoretical Characteristics and Promotion of the Educationist Spirit - LI Lingyu; DONG Jun (Jiaoshi jiaoyu xuebao)
As the value ideal and spiritual engine for building a strong teaching force, the educationist spirit serves as the core driving force propelling the teaching profession toward high-quality development. Educationalist spirit with Chinese characteristics embodies the essence of Marxist educational theory, carries forward the profound heritage of outstanding traditional Chinese teacher ethics, and aligns with the urgent need to forge a high-quality teaching workforce in the new era. It is characterized by a distinct theoretical character, profound cultural heritage, and strong practical relevance. The educationist spirit demonstrates a steadfast commitment to nurturing talents for the Party and the nation, practices a people-centered philosophy of educational development, reflects the spiritual ethos and historical mission of Chinese teachers in the new era, and showcases pronounced political orientation, people-centeredness, and contemporary relevance. To promote the educationist spirit in the new era, it is essential to balance external norms with internal motivation, integrate traditional methods with modern technology, and emphasize three-dimensional synergy: multi-stakeholder collaboration, institutional innovation, and empowerment through modern technology. This approach will ensure the rootedness, flourishing, and enduring vitality of the educationist spirit.